2023
DOI: 10.29011/2574-7754.101349
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Observational Study on the Effectiveness of Segmental Spinal Anesthesia in Patients Posted for Modified Radical Mastectomies

Abstract: Background: Modified radical mastectomy is a treatment of choice in patients having carcinoma breast. The higher chances of complications with general anesthesia lead to a change in our clinical practice towards regional anesthesia. The current literature revealed that the maximum distance between the dura mater and the spinal cord is at the mid-thoracic level, but very few studies are advocating for the use of segmental spinal anesthesia for modified radical mastectomies. Therefore, the present study is plann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 20 publications
2
7
0
Order By: Relevance
“…Another possible mechanism is the presence of low CSF volume and thinner nerve route at the thoracic level and sparing of the lower extremities led to less vasodilatation in comparison to the block at the lumbar leve l2 . Fewer hemodynamic alterations were also reported in the other studies 2,13,14,23 .…”
Section: Discussionsupporting
confidence: 70%
See 4 more Smart Citations
“…Another possible mechanism is the presence of low CSF volume and thinner nerve route at the thoracic level and sparing of the lower extremities led to less vasodilatation in comparison to the block at the lumbar leve l2 . Fewer hemodynamic alterations were also reported in the other studies 2,13,14,23 .…”
Section: Discussionsupporting
confidence: 70%
“…van Zundert et al3 and Heisnam et al 21 also observed minimal side effects in segmental thoracic spinal anaesthesia for laparoscopic cholecystectomy. Paliwal et al 2 and Chandra et al 14 also reported fewer unwanted effects in thoracic segmental block for breast surgery. Paresthesia is not desired but can occur with any technique of spinal anaesthesia.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations